Heartbreak ridge - Eastwood, Clint 1930-; Carabatsos, Jim; Niehaus, Lennie; Mason, Marsha; Van Peebles, Mario (Clint Eastwood collection)
There are no wars to fight. But Gunnery Sgt. Tom Highway, a dog-faced relic of past wars, still has a lot of fight in him. He is a Marine Corps lifer who started his last tour of duty before retirement, and sees the bumpy road his life has taken become more complicated, due to feisty recruits, by-the-book officers, and a salty ex-wife to whom he's still attracted.